Prevalence of temporomandibular dysfunction and pain syndrome and associated factors in dental students - Martínez, Luisa; Mendivelso, Cindy; Bustamante, Paula; Sánchez, César; Sarrazola, Ángela (Revista Estomatología, 2015)
Background: Temporomandibular joint dysfunction and pain syndrome (TMJD) has been identified as one of the principle causes of non-dental pain in the orofacial region. Objective: To describe the prevalence of TMJD and associated factors in the students of the faculty of odontology of the University Cooperativa de Colombia (UCC), Envigado campus. Materials and methods: Observational, descriptive and cross-sectional study. 98 randomly selected students were evaluated. A survey, clinical examination, Helkimo index, emotional distress and anxiety test was performed. Univariate and bivariate analysis was performed (Chi2, p<0,05). Results: 66% were women. The average age was 21 years (SD±3). 26,5% had dental clenching habit, 26,5% and 18,4% onicofagia bruxism. 31,6% reported joint click, 30,6% headache or neck pain, 18,4% pain in the temporomandibular joint (TMJ) and 12,2% mandibular stiffness. Clinically, 44,5% presented unilateral chewing. 62,2% showed deviation on opening and 81,6% on closing. 42,9% had anxiety disorder and to a lesser extent panic disorder. 74,7% had mild TMJD. No difference was found with statistical significance between the prevalence of sex TMJD. (Chi2, p=0,255) or any association with anxiety disorders (Chi2, p=0,060), and distress. Conclusions: Mild TMJD was most frequent among the student population. Clenching habits, nail biting and unilateral chewing were identified. No difference was found by gender or any association with anxiety disorder or anxiety. Particularly striking is the high prevalence of unilateral chewing and anxiety disorder, which are important to study.